2015
DOI: 10.1159/000367756
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics of Patients with Cryptogenic Hepatocellular Carcinoma in a Hepatitis B Virus-Endemic Area

Abstract: Objectives: Chronic hepatitis B virus (HBV) infection is the most common cause of hepatocellular carcinoma (HCC) in South Korea, but a high prevalence of metabolic diseases may result in increases in the incidence of cryptogenic HCC (cHCC). We studied characteristics of the cHCC in a single-center cohort. Methods: A cohort of 1,784 HCC patients newly diagnosed and treated at the National Cancer Center, Korea, between 2004 and 2009 was reviewed and analyzed. Results: The cause of HCC was categorized as cHCC, HB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 45 publications
0
13
1
Order By: Relevance
“…In this study, we analyzed a total of 447 consecutive NBNC HCC patients (13.4%) among 3,347 HCC patients registered in our institution. The proportion of NBNC HCC patients was slightly lower than the proportion reported from other hospitals in Korea, which ranged from 16.1% to 20.2% [5,17], and was also lower than that indicated by the nationwide cohort study in Korea, which reported an NBNC HCC prevalence of 27.4% [3]. In our cohort, the most common potential etiology of NBNC HCC was heavy alcohol use (n = 267, 59.7%).…”
Section: Discussioncontrasting
confidence: 76%
See 2 more Smart Citations
“…In this study, we analyzed a total of 447 consecutive NBNC HCC patients (13.4%) among 3,347 HCC patients registered in our institution. The proportion of NBNC HCC patients was slightly lower than the proportion reported from other hospitals in Korea, which ranged from 16.1% to 20.2% [5,17], and was also lower than that indicated by the nationwide cohort study in Korea, which reported an NBNC HCC prevalence of 27.4% [3]. In our cohort, the most common potential etiology of NBNC HCC was heavy alcohol use (n = 267, 59.7%).…”
Section: Discussioncontrasting
confidence: 76%
“…Adam et al [28] reported that hepatocarcinogenesis in a non-cirrhotic liver was associated with a reduced number of clonal hepatocellular patches, analogous to aging-related changes, which may explain the older age at diagnosis in the absence of cirrhosis in many NBNC-NA-NO patients. Another study from Korea also reported that patients with cryptogenic HCC were much older than those with HCC associated with other etiologies [17]. However, the outcome of NBNC-NA-NO HCC was similar to NBNC-A HCC, despite several differences in baseline characteristics.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Failure to properly treat AIH and DILI could result in clinically devastating acute or chronic outcomes [5,6] . Chronic AIH could also lead to hepatocarcinogenesis in the future [9][10][11] .…”
mentioning
confidence: 99%
“…However, among the 14 studies entered into the systematic review, the era of the cohorts, observation periods, the proportion of patients with hepatitis viral infection (hepatitis B virus infection, HCV infection, and non-B non-C hepatitis), and the proportion of patients with liver cirrhosis were heterogeneous. It is well known that the recurrence pattern and survival after curative treatments differ according to underlying hepatic diseases such as the viral infection status [10][11][12][13]. However, the aforementioned 14 studies did not evaluate the effects of antiviral therapies even though controlling viral infections with antiviral therapies decreases postoperative HCC recurrence after hepatic resection [14,15].…”
Section: Introductionmentioning
confidence: 99%